A 10 year review of total laparoscopic hysterectomy in Hospital Sultan Abdul Halim Sungai Petani, Kedah - Zakaria, Muhammad Noor Asyraf (2020)
Objective To analyse surgical outcomes of total laparoscopic hysterectomy (TLH) for benign disease. Methods Retrospective analysis of 369 cases collected from January 2008 to December 2017 of women who underwent TLH in Hospital Sultan Abdul Halim, Sungai Petani. Clinical, demographic, surgical, and intra and perioperative data were recorded. Results Patients had a mean age of 44.7 (±2.6) years, a mean of 2.6 (±1.5) pregnancies, and a mean BMI of 31.2 (±11.4) kg/m2. The mean surgical duration was 89.1 (±20.9) minutes, with mean blood loss of 149 (±152) mL and average hospital stay of 2.2 (±0.5) days. Mean uterine size was 13.7 (±2.5) weeks of gestation. Main indication for TLH was uterine fibroid (55.6%). Of 369 patients, 10 (2.71 % ) were converted to laparotomy. Reasons for conversion were severe adhesive disease (6 patients), bowel injury (3 patients) followed by inadequate visualization secondary to fibroids (1 patient). Bladder injury occurred in 4 (1.08%) patients. No patient developed major postoperative complication. No significant differences were seen in the intraoperative and postoperative complication rates of patients who were obese (body mass index ≥30 kg/m2) or patients with enlarged uterus (≥ 12 weeks gestation). There is significant difference in term of duration of operation in patients with previous caesarian section or pelvic surgery but there is no significant difference in term of intraoperative and postoperative complication rates. Conclusions Total laparoscopic hysterectomy can be performed successfully in most patients with benign indications. It is a procedure with a low incidence of complications.